Waste Biorefinery: A New Paradigm for a Sustainable Bioelectro Economy. Issue 11 (November 2016) - Mohan, S. Venkata; Butti, Sai Kishore; Amulya, K.; Dahiya, Shikha; Modestra, J. Annie
Abstract : A waste biorefinery is a means to valorize waste as a renewable feedstock to recover biobased materials and energy through sustainable biotechnology. This approach holistically integrates remediation and resource recovery. Here we discuss the various technologies employable to construct a waste biorefinery platform and its place in a biobased economy.